Artificial Intelligence & Collusion: When Computers Inhibit Competition - Ezrachi, A; Stucke, M (University of Illinois, 2017)
The development of self-learning and independent computers has long captured our imagination. The HAL 9000 computer, in the 1968 film, 2001: A Space Odyssey, for example, assured, “I am putting myself to the fullest possible use, which is all I think that any conscious entity can ever hope to do.” Today businesses (and governments) are increasingly relying on big data and big analytics. As technology advances and the cost of storing and analyzing data drops, companies are investing in developing ‘smart’ and ‘self-learning’ machines to assist in pricing decisions, planning, trade, and logistics. Furthermore, with the Internet of Things, more of our daily activities will be collected and used to enhance (or exploit) our immediate living environment – the way we commute, shop and communicate. These developments are accompanied by advances in Artificial Intelligence (AI). That is, the development of software and computers capable of self-learning and intelligent behavior. Naturally, these developments raise many challenging legal and ethical questions as to the relationship between man and machine, humans’ control—or lack of it—over machines, and accountability for machine activities. While these issues have long captivated our interest, few would envision the day when these developments (and the legal and ethical challenges raised by them) would become an antitrust issue.